1999
DOI: 10.1136/hrt.82.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage: structure, function, and role in thromboembolism

Abstract: The left atrial appendage (LAA) is derived from the left wall of the primary atrium, which forms during the fourth week of embryonic development. It has developmental, ultrastructural, and physiological characteristics distinct from the left atrium proper. The LAA lies within the confines of the pericardium in close relation to the free wall of the left ventricle and thus its emptying and filling may be significantly aVected by left ventricular function. The physiological properties and anatomical relations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
375
1
19

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(427 citation statements)
references
References 67 publications
9
375
1
19
Order By: Relevance
“…LAA develops as a residue originating from LA at 4 weeks of embryonic development. Although the ultrastructural and physiological characteristics of LAA develop independently from LA in this process, muscle cell structures and the myocardium of both structures are similar [22]. Thus, as a component of LA, LAA functions are thought to be reflected by LA structural and functional parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAA develops as a residue originating from LA at 4 weeks of embryonic development. Although the ultrastructural and physiological characteristics of LAA develop independently from LA in this process, muscle cell structures and the myocardium of both structures are similar [22]. Thus, as a component of LA, LAA functions are thought to be reflected by LA structural and functional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, the highly dynamic LA and LAA structure prevents stasis. In case of its dysfunction, SEC and/ or thrombus formation may develop in association with increased stasis [22,23]. LAA develops as a residue originating from LA at 4 weeks of embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) As the LAA represents one of the major sources of cardiac thrombus formation responsible for stroke in patients with AF, 5,6) the imaging of the different structures and lobes is of utmost importance to diagnose the presence of thrombus, especially in patients with non-valvular AF. 7,8) Multidetector computed tomography 9) and contrast-enhanced magnetic resonance imaging 10) are able to image the LAA; however, it was concluded that magnetic resonance imaging lacks diagnostic accuracy for the detection of LAA thrombi.10) Transesophageal echocardiography (TEE) is the gold standard to detect LAA thrombus, 11) but false positive results still occur.12) In this study, we evaluated the LAA structure and functions by TEE in patients with non-valvular AF (both chronic and paroxysmal types) to study the possible association between the different LAA morphologies and functional changes with the patients' history of ischemic cerebral stroke. …”
mentioning
confidence: 99%
“…The left atrium (LA) and the LAA are important locations that are frequently associated with thrombus formation and subsequent cardioembolic events, particularly in association with dysrhythmias, such as AF [20,21]. An estimated 47% of thrombi in valvular AF and 91% of those in nonvalvular AF are located in the LAA [22].…”
Section: La or Laa Thrombusmentioning
confidence: 99%